Model of Indonesia-Timor Leste Land Border Management by Optimizing the Cross-Border Post in Belu Regency, East Nusa Tenggara - Iva Rachmawati; Fauzan Djalaludin (Global Strategis, 2016)
This article is based on our research on the management of Cross-Border Posts (CBPs) in Belu that was conducted in three Cross Border Posts: Mota’ain, Motamasin and Turiskain. We offer a model of CBP management with two changes to the initial function design embedded with CBP (CIQS/Custom, Immigration, Quarantine and Security). The changes we offer are: (1) withdrawing the military personnel; and (2) assigning a new social function. These changes are based on the facts of local’s historical, social and economic backgrounds which are different from those of other areas. This approach will absolutely affect the form of the current CBP. Interviews were conducted to collect information related to the socio-cultural backgrounds and economic needs among the people living around the border. With the changes in mind, functions, it is expected that the CBP can meet the need of the people living around the border.